The Antiproliferative Activity of a Mixture of Peptide and Oligosaccharide Extracts Obtained from Defatted Rapeseed Meal on Breast Cancer Cells and Human Fibroblasts - Romina Lis Ferrero; Caroline Ruth Weinstein-Oppenheimer; Zaida Cabrera-Muñoz; María Elvira Zúñiga-Hansen (Foods, 2023)
Oligosaccharide and peptide extracts obtained separately from defatted rapeseed meal (DRM) have shown antiproliferative activities on the MCF-7 breast cancer cell line. However, oligosaccharide extracts were not tested on human fibroblasts and have low yields. The objective of the present study was to combine two antiproliferative extracts, the peptides and oligosaccharides, that were obtained independently with commercial enzymes from DRM, allowing improvement of the mass yield and antiproliferative activity. The DRM was solubilized in an alkaline medium to obtain an insoluble meal residue (IMR) and an alkaline extract (RAE). To produce the oligosaccharide extract from IMR, three enzymes and different enzyme/substrate ratios were used. The oligosaccharide extract (molecular weight <30 kDa) recovered with the commercial enzyme. Endogalacturonase showed an 80% inhibition on MCF-7 cells at 20 mg/mL. The combination of this oligosaccharide extract with the peptide extract (obtained with Alkalase 2.4 L from a RAE at 10 mg/mL) inhibited 84.3% of MCF-7 cells proliferation at a concentration of 20 mg/mL, exhibiting no cytotoxic effects on fibroblasts. The mass yield of the extract pool was 27.07% (based on initial DRM). It can be concluded that a mixture of antiproliferative extracts was produced from DRM which was selective against MCF-7 cells.